(untitled) (Bangladesh Agronomy Journal, 2020)
The study was conducted at the farmer’s field in Sylhet under AEZ 20 during three consecutive years 2016-17, 2017-18 and 2018-19 to determine the productivity and profitability of cropping patterns viz. IP: improved pattern (Mustard-T. Aus-T. Aman rice) by introducing high yielding varieties and improved management practices and FP: farmer’s pattern (Fallow-T. Aus-T. Aman rice). The experiment was laid out in randomized complete block design with six dispersed replications. Results showed that the improved pattern with management practices provided 6.88 and 22.84 % higher grain yield of T. Aus and T. Aman rice, respectively; also contributed higher mean rice equivalent yield (9.44 t ha-1) compared to farmer’s pattern.Sustainable yield index (0.36), production efficiency (39.75 kg ha-1day-1), and land use efficiency (75.98 %) were maximum in Mustard-T. Aus- T. Aman rice cropping system on an average. Similarly, the highest mean gross margin (Tk.1,12,425 ha-1) with benefit cost ratio (2.13) was obtained from improved pattern. Three years results revealed that 24% extra cost provides an ample scope of considerable improvement of the productivity with the inclusion of Mustard before T. Aus rice in improved pattern. Bangladesh Agron. J. 2019, 22(2): 1-10